Orientin Ameliorates LPS-Induced Inflammatory Responses through the Inhibitory of the NF-κB Pathway and NLRP3 Inflammasome - Xiao, Qingfei (Evid Based Complement Alternat Med, 2017)
Inflammation is a complex response to diverse pathological conditions, resulting in negative rather than protective effects when uncontrolled. Orientin (Ori), a flavonoid component isolated from natural plants, possesses abundant properties. Thus, we aimed to discover the potential therapeutic effects of orientin on lipopolysaccharide- (LPS-) induced inflammation in RAW 264.7 cells and the underlying mechanisms. In our studies, we evaluated the effects of Ori on proinflammatory mediator production stimulated by LPS, including tumor necrosis factor- (TNF-) α, interleukin- (IL-) 6, IL-18, and IL-1β, along with prostaglandin E(2) (PGE(2)) and NO. Our data indicated that orientin dramatically inhibited the levels of these mediators. Consistent with these results, the expression levels of cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) were also reduced. Further study demonstrated that such inhibitory effects of Ori were due to suppression of the nuclear factor-kappa B (NF-κB) pathway and nucleotide-binding domain- (NOD-) like receptor protein 3 (NLRP3) inflammasome activation, which may contribute to its anti-inflammatory effects. Together, these findings show that Ori may be an effective candidate for ameliorating LPS-induced inflammatory responses.